The Effect of Teachers' Professional and Pedagogical Competencies on Students' Mathematics Learning Outcomes at Madrasah Ibtidaiyah - Anggun Putri Yunanti; Aam Amaliyah (Indonesian Journal of Innovative Teaching and Learning, 2025)
Background: Competence is the ability or proficiency of a person that still exists in the form of self-potential. In the context of education, teacher competence plays a vital role in influencing student learning outcomes. Objective: The purpose of this study was to determine the effect of the professional and pedagogical competence of teachers on student learning outcomes in Madrasah Ibtidaiyah Negeri 02 Lebong. Method: This research used an ex post facto approach and was conducted in 2023. The sample consisted of 24 students. Data were collected through questionnaires and documentation. Data analysis included normality tests, homogeneity tests, and paired t-tests. Result: The results revealed that teachers' professional and pedagogical competencies significantly affect students' mathematics learning outcomes. Conclusion: Teacher competence, both professional and pedagogical, has a measurable impact on improving student learning outcomes at Madrasah Ibtidaiyah Negeri 02 Lebong. Contribution: The findings of this study are expected to provide useful insights and scientific contributions to the field of education, particularly in Madrasah Ibtidaiyah, by enriching knowledge about the influence of teacher competence on student academic achievement.